A Systematic Literature Review and Bibliometric Analysis of Crisis Communication in Digital Media (2015–2025): Mapping Trends and Intellectual Structures - Waskito Aji, Tofa; Hastjarjo, Sri; Hermawati, Tanti (Jurnal Audiens, 2026)
This study maps the trends and conceptual structure of crisis communication in digital media (2015–2025). Anchored in crisis/risk communication, platform/medium perspectives, and trust-building, we conduct a PRISMA-guided systematic literature review using Covidence. A Scopus query produced 76 records; after screening, 19 journal articles met the inclusion criteria (English, OA, article, final stage). We perform bibliometric mapping using VOSviewer and code outlet quartile, research method, organization type, social media platform, and yearly output. Four reproducible clusters emerge: (i) a public-health core (public health, epidemiology, procedures); (ii) social-media–trust–netnography; (iii) crisis management/risk communication with network analysis and fake news; and (iv) public relations/digital communication. Reflecting a significant pandemic-driven surge (84.2% of publications during 2021–2025), high-quality (Q1/Q2) research predominantly employs computational and netnographic methods on Twitter/X and multi-platform settings to address COVID-19 as a thematic anchor linking health communication, platform orchestration, and disinformation. The synthesized literature highlights orchestration-on-platform, trust-by-design, and evidence-based counter-misinformation as critical pillars emphasized for navigating digital crises; future research should extend to non-health crises, short-form/video platforms, and causal/longitudinal designs.